Christian-Muslim Dialogue Perspectives of “The Muslim View of Christology” and “To Be a European Muslim” - Jen-Chien Lin (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
Mahmoud Ayoub and Tariq Ramadan are Islamic scholars working on a Muslim-Christian dialogue study. They proposed the concepts of “ The Muslim View of Christology” and “ To Be a European Muslim”, respectively, and promoted the study of the Muslim-Christian dialogue into a broader field with far-reaching influence. The purpose of this study is to compare the concepts of “ The Muslim View of Christology” and “To Be a European Muslim” , as well as to understand the meaning and contextualization of the dialogue between the Shi?i and the Sunni within the Muslim-Christian dialogue, in order to seek a new dimension of religious dialogue. The method of this study is a systematic analysis. This entails a close reading of the two thinkers? writings on Christian-Muslim encounters, in order to make a comprehensive presentation of their thinking about the Christian-Muslim dialogue in its many dimensions, considering these structures through assessing their inner consistency; in particular, including the viewpoint of “The Muslim View of Christology” and “To Be a European Muslim”. “The Muslim View of Christology”, Ayoub emphasizes, Christians must take as a Muslim view and accept it as such, at least as the methodological basis for their research studies. Ramadan prioritizes Qur'anic interpretation over simply reading the text, in order to understand its meaning and to practice the tenets of Islamic philosophy. He proposed the following perspective: To be a European Muslim and to research the Study of Islamic Sources in the European Contextualisation. We find “the Muslim view of Christology” as a blessing, as a sign of God?s abundant generosity in the phenomenon of diversity. The idea that “To Be a European Muslim” is an Islamic worldview is a trend that is universal and rooted in the land. Christian-Muslim dialogue on these two topics is a very indicative key and can contribute to peace in this world. The Christology of this study will be limited to“the Muslim View of Christology” and will limit Muslims to Muslim communities born in Europe. In the context of Abraham’s religion, the purpose of the Christian-Muslim dialogue should be courageous and dare to ascend to the model of coexistence and the unity of God, not just for each others’ tolerance and acceptance. This is the ultimate concern for religious dialogue between Christianity and Islam.